1999
DOI: 10.1093/ajcn/69.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Wine intake and diet in a random sample of 48763 Danish men and women

Abstract: Wine drinking is associated with an intake of a healthy diet. This finding may have implications for the interpretation of previous reports of the relation between type of alcoholic beverage and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
149
3
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(168 citation statements)
references
References 20 publications
13
149
3
3
Order By: Relevance
“…In contrast, other investigations conducted outside the Mediterranean area, such as the United States or Northern Europe have reported that wine drinkers tended to adopt healthier dietary patterns (Tjønneland et al, 1999;Barefoot et al, 2002;McCann et al, 2003). In the American study, wine drinkers reported eating more fruit and vegetables and fewer servings of red or fried meats (Barefoot et al, 2002).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In contrast, other investigations conducted outside the Mediterranean area, such as the United States or Northern Europe have reported that wine drinkers tended to adopt healthier dietary patterns (Tjønneland et al, 1999;Barefoot et al, 2002;McCann et al, 2003). In the American study, wine drinkers reported eating more fruit and vegetables and fewer servings of red or fried meats (Barefoot et al, 2002).…”
Section: Discussionmentioning
confidence: 65%
“…Similarly published data from a western New York study showed that wine drinkers tended to consume more fruits, vegetables, and grains, and somewhat lower amounts of meats (McCann et al, 2003). In a Danish study wine drinkers tended to have a higher intake of fruits, fish, vegetables, salads and to be more likely to use olive oil for cooking (Tjønneland et al, 1999). Nevertheless, in the aforementioned countries wine is an expensive alcoholic beverage which is bought by individuals belonging to higher socioeconomic levels who are more likely to have healthier dietary practices (Marques-Vidal et al, 2000;Mortensen et al, 2001;Barefoot et al, 2002;McCann et al, 2003;Nielsen et al, 2004;Ruidavets et al, 2004).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Wine itself appears to add an independent CV benefit to this diet (Grønbaek et al, 2000). However, despite reports indicating that light-to-moderate alcohol consumption reduces both CV mortality (Thun et al, 1997) and the risk of stroke (Berger et al, 1999), wine drinking also has been related to the intake of healthier diets (Tjonneland et al, 1999) and other advantageous lifestyle characteristics (Wannamethee & Shaper, 1999), to which CV benefits are attributed. Thus, the health benefits of phenolic acids and polyphenols contained in red wine may be indiscernible in populations that ingest large amounts of fruit and vegetables, whereas these benefits could be distinctly apparent in populations with relatively low intakes of these kinds of foods (de Lorgeril et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, moderate drinkers tend to smoke less than other groups (Marques-Vidal et al, 1995), while hypertension control is inversely related to alcohol consumption (Lang et al, 1987). In addition, wine-drinking populations tend to have a healthier diet than those which consume other alcoholic beverages (Evans et al, 1995;Tjùnneland et al, 1999), whereas the bingeing style of drinking beer has been associated with a higher risk of death from any cause (including cardiovascular disease; Kozarevic et al, 1983;Kauhanen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%